Potential Probiotic Yeasts of the Pichia Genus Isolated from ‘Dadih’, a Traditional Fermented Food of West Sumatra, Indonesia - Chihombori, Tatenda Calvin; Mustopa, Apon Zaenal; Astuti, Rika Indri; Mutiara, Ilma; Refli, Redoyan; Umami, Rifqiyah Nur; Fatimah; Irawan, Herman; Ekawati, Nurlaili; Trinugroho, Joko P; Akmaliyah, Rizna; Chairunnisa, Sheila; Amani, Febriyanti Nur; Manguntungi, Baso; Hertati, Ai; Mamangkey, Jendri (HAYATI Journal of Biosciences, 2025)
Fermented buffalo milk, known as dadih, serves as a reservoir of potential probiotic yeasts. Over the past two decades, probiotic yeasts have gained increasing attention in both basic and clinical sciences due to their health benefits. This study aimed to isolate and characterize probiotic yeasts from dadih. Yeasts were isolated using yeast Extract, peptone, and dextrose (YPD) medium, and molecularly identified through 18S-rRNA sequencing. Probiotic potential was assessed by evaluating resistance to acidic pH, bile salts, proteolytic, lipolytic, and hemolytic activities. Secondary metabolites produced during fermentation were tested for antimicrobial properties. GBT30 and GBT37 isolates were selected based on their superior performance in probiotic property assays for further analysis. Molecular identification revealed these isolates as Pichia occidentalis (GBT30) and Pichia kudriavzevii (GBT37). Both strains demonstrated in vitro survivability under simulated gastrointestinal conditions and exhibited antimicrobial activity. Whole-genome sequencing of P. kudriavzevii GBT37 identified a genome size of 10,906,850 base pairs, distributed across four chromosomes with a GC content of 38.26%. Notably, secondary metabolite biosynthesis genes were located on contig 7. In addition, 26 probiotic-related genes, including GSY1, HSC82, HSP104, TPS1, ARN1, FLO1, ALA1, SIR2, and others, were identified in P. kudriavzevii GBT37, indicating its potential as a probiotic yeast. The traditional fermentation process of dadih offers probiotic yeasts with promising health benefits, supporting its potential as a functional food.